Terrorism Index analysis "number of dead" and its impact on the Iraq Stock Exchange indicators Applied research in a sample of Banks listed on the Iraq Stock Exchange - Nagham Hussein Neama; Wejdan Hussein Obaid (Iraqi Journal for Administrative Sciences, 2024)
The subject of research seeks to analyze the "political risk component, of terrorism Index "Which consists of five indicators, number of terrorist operations, number of dead and wounded, the size of financial losses, the search depends on analyzing the sub-index number of dead for terrorism Index and its impact on the indicators listed on the Iraq Stock Exchange. The research findings have produced that the number of dead index significantly affect with the rate of (49%), which is explained by the proportion of the number of dead from the changes in the Iraq Stock Exchange indices variable, and the rest amounting of (51%) is attributed to the contribution of other variables affect those indicators away from terrorism indicators. As for the practical side it has been used the style of gradient and correlation on the sample represented by ten banks listed on the Iraq Stock Exchange and reported the correlation and interaction between the study variables